Development of an automated greenhouse for plants - Soares , Ana Caroline Meireles; Sousa , Jhonatan Peres de; Oliveira , Gielson Vitor; Lira , Rivânia da Silva; Borges , Josimar Hendrio Ferraz (Seven Editora, 2023)
This project proposes the development of a didactic plant (greenhouse) for monitoring and automating the variables of temperature, humidity, and luminosity through the Arduino, aiming at the development of a plant in a protected environment and on a reduced scale. As a project methodology, an automated prototype for greenhouses based on the Arduino platform was implemented, which receives information from the sensors and compares it with the pre-selected parameters, making it always follow the established measures for the good development of the crop in question. It is concluded that the simulations produced are fundamental to verify the response mode of the didactic plant in different conditions, chosen materials, and worked parameters, as well as allowing to guide the research group, regarding the ideal conditions for the development of the plant. Studies of this nature enable the development of domestic greenhouses combined with automation techniques, in addition to making plant production accessible and efficient in small-scale protected environments. DOI:https://doi.org/10.56238/devopinterscie-173